A simulative framework for a multi-regional assessment of local energy markets – A case of large-scale electric vehicle deployment in Germany. (1st October 2021) - Cramer, Wilhelm; Schumann, Klemens; Andres, Michael; Vertgewall, Chris; Monti, Antonello; Schreck, Sebastian; Metzger, Michael; Jessenberger, Stefan; Klaus, Joachim; Brunner, Christoph; Heringer, Florian; Alvarado, Axel; et al.
Highlights: Multi-regional LEM Assessment. High penetration of Evs. Modeling of energy systems. Abstract: The increasing share of distributed energy resources gives rise to new opportunities for deploying innovative business models and coordination schemes within sustainable energy systems. Different concepts entail different implications at socioeconomic, technical and institutional level. Hence, their thorough assessment is key to understanding their actual potential as enablers of the energy transition. Considering this background, we focus on local energy markets as an increasingly discussed approach for coordinating distributed energy systems and introduce a simulative framework for enabling a multi-regional assessment of this concept. Local energy markets bear the potential for increasing the active participation of end consumers, which could increase their acceptance for energy projects in general and their returns on investment, as well as for reducing the peak load on increasingly congested electrical grids by enhancing local energy balancing. We evaluate these hypotheses for twelve representative German regions, for which we formulate assumptions regarding the energy demand as well as the shares of distributed energy resources that are consistently aligned with an overall European energy scenario envisaging a rapid growth of electric vehicles in Germany. For this purpose, we enhance an existing framework for the assessment of local energy markets in order to be able to include the flexibility of the electric mobility sector in local trade activities. The simulation results show that local energy markets have a significant impact on energy systems: First, local trading increases the economic benefits over all participants, who would otherwise only be able to use their generation for self-consumption or direct marketing in central energy markets. Second, local energy balancing increases on average by 60 % over all regions. Third, infrastructural relief of the overlaying transmission grids can be accomplished by reducing the yearly peak load at the point of common coupling by 39 % on average and at the most by 97 % . Furthermore, we find that including electric vehicles in local market activities does not alter but rather reinforces these effects.